A Proposed Instrument for Mapping Teacher Digital Competence: Design and Conceptual Framework - Kewajiban, Tepati Hak (Jurnal Studi Guru dan Pembelajaran, 2025)
The digital transformation in education has created an urgent need for reliable instruments to map Teacher Digital Competence (TDC), particularly for in-service K–12 teachers. This urgency is heightened by the demands of 21st-century pedagogy, which emphasizes technological proficiency to support effective, inclusive, and sustainable learning. This study aims to develop the conceptual design and initial structure of a comprehensive, multidimensional TDC mapping instrument. The proposed instrument suite consists of two main components: a quantitative survey and a qualitative semi-structured interview protocol, both constructed around five core dimensions of TDC: Digital Pedagogy and Learning Design, Digital Resource Management and Creation, Digital Assessment and Feedback, Professional Engagement and Collaboration in Digital Environments, and Ethical and Responsible Digital Citizenship in Education. The instrument development employed an extensive literature review approach, synthesizing insights from leading theoretical models, including DigCompEdu, INTEF, COMDID, and other contemporary research. The primary outcome of this research is a systematically structured TDC mapping instrument equipped with measurable and context-relevant indicators. It is designed to support a mixed-method research approach, enabling the collection of both quantitative and qualitative data for deeper analysis. Although the instrument is currently at the conceptual stage, it holds significant potential for application in TDC mapping studies, evaluations of professional development programs, and the formulation of data-driven educational policies. Further empirical validation is recommended prior to broader implementation